Halogen Bonding Helicates Encompassing Iodonium Cations. (5th June 2019) - Vanderkooy, Alan; Gupta, Arvind Kumar; Földes, Tamás; Lindblad, Sofia; Orthaber, Andreas; Pápai, Imre; Erdélyi, Máté
Abstract: The first halonium‐ion‐based helices were designed and synthesized using oligo‐aryl/pyridylene‐ethynylene backbones that fold around reactive iodonium ions. Halogen bonding interactions stabilize the iodonium ions within the helices. Remarkably, the distance between two iodonium ions within a helix is shorter than the sum of their van der Waals radii. The helical conformations were characterized by X‐ray crystallography in the solid state, by NMR spectroscopy in solution and corroborated by DFT calculations. The helical complexes possess potential synthetic utility, as demonstrated by their ability to induce iodocyclization of 4‐penten‐1‐ol. Abstract : Halogenium‐Helices : Iodonium‐Kationen werden durch Dreizentren‐Vierelektronen‐Halogenbindungen des Typs [N−I−N] + mit oligomeren Pyridyl‐Liganden stabilisiert. Die Komplexierung des Iodonium‐Ions produziert neue helikale Strukturen, wie durch DFT‐Berechnungen vorhergesagt und durch Röntgenkristallographie sowie NOE‐Spektroskopie bestätigt wurde. Die Helices sind reaktiv in Halofunktionalisierungsreaktionen.